The Effectiveness of Android-Based Physics Learning Media Assisted by Smart Apps Creator to Improve Learning Outcomes - Wisnu Watin; I Wayan Gunada; Husrin Fauzia; Syahrial Ayub (Prodi Fisika FKIP Unram, 2023)
The aim of the research is to develop physics-based learning media based on Android with the help of smart app creators on mechanical wave material. Tests were conducted to determine the effectiveness of the media to improve student learning outcomes. This study uses the Research and Development (R&D) development research method. The research subjects were 22 students of SMAN 1 Gunungsari class XI IPA1. The results obtained were an average pre-test score of 43.33 and a post-test score of 72.50, with an average N-gain of 0.52 which qualified in the medium category. This shows that the Android-based physics learning media assisted by smart app creators is effective in improving student learning outcomes in mechanical wave material. Keywords: physics learning media, smart apps creator, learning outcomes.